Anhydrobiosis in yeast: Glutathione overproduction improves resistance to dehydration of a recombinant Ogataea (Hansenula) polymorpha strain. (August 2018) - Kulikova-Borovikova, Diana; Khroustalyova, Galina; Chang, Chuang-Rung; Daugelavicius, Rimantas; Yurkiv, Mariana; Ruchala, Justyna; Sibirny, Andriy; Rapoport, Alexander
Graphical abstract: Highlights: Recombinant yeast strain O. polymorpha with glutathione overproduction is resistant to dehydration. New immobilisation method may be used for the storage of recombinant O. polymorpha. Besides membrane lipids glutathione may protect membrane proteins and nucleic acids. Abstract: We show for the first time that a recombinant strain of yeast Ogataea (Hansenula) polymorpha is at least as tolerant to dehydration-rehydration treatment as the wild type strain. It is believed that this unusual characteristic of this recombinant yeast strain is linked with its ability to overproduce glutathione. Based on plasma membrane permeability analysis, we hypothesise that glutathione, in addition to its powerful antioxidative protective effects on membrane lipids, may also protect membrane proteins and/or nucleic acids. The combination of yeast cell dehydration with immobilisation and subsequent preliminary slow rehydration in water vapour gave good results in terms of recombinant strain cell viability in the dry state. Correspondingly, this recombinant strain can be used efficiently in the industrial production of glutathione.